Comparison of in vitro Neuronal Differentiation Capacity Between Mouse Epiblast Stem Cells Derived From Nuclear Transfer and Naturally Fertilized Embryos - Li, Tong; Zheng, Yi; Li, Yan; Ye, Danna (Frontiers in Molecular Neuroscience, 2018)
Somatic cell nuclear transfer (SCNT) can give rise to fertile adults, but the successful perinatal and postnatal developmental rates are inefficient, including delayed developmental behaviors and respiratory failure. However, the molecular and cellular mechanisms remain elusive. Mouse epiblast stem cells (mEpiSCs) from E5.5-6.5 epiblasts share defining features with human embryonic stem cells (hESCs), providing a new opportunity to study early mammalian development in vitro. In this study, mEpiSCs were established from naturally fertilized mouse embryos (F-mEpiSCs) and SCNT mouse embryos (NT-mEpiSCs). Also, the in vitro neuronal differentiation capacity of F-mEpiSCs and NT-mEpiSCs was compared. Morphology analysis showed less and smaller neurospheres formation and lower percentage of early neurons generation in NT-mEpiSCs. The immunocytochemical analysis and altered mRNA expression levels of the neuronal markers in differentiated cells further confirmed that neurogenesis was slower in NT-mEpiSCs than in F-mEpiSCs. Moreover, neuronal differentiation capacity was correlated with the basal expression levels of Atox1 and Vinculin but not Brachyury and Otx2, emphasizing that developmental aberrations in neurogenesis were associated with the NT technique but not random variations between clones. This study provided an important in vitro platform using mEpiSCs to study early epigenetic and developmental processes associated with neurogenesis.